2001
DOI: 10.1111/1468-0084.00234
|View full text |Cite
|
Sign up to set email alerts
|

Break Point Estimation and Spurious Rejections With Endogenous Unit Root Tests

Abstract: This paper examines the accuracy of break point estimation using the endogenous break unit root tests of Zivot and Andrews (1992) and Perron (1997). We find that these tests tend to identify the break point incorrectly at one‐period behind (TB‐1) the true break point (TB), where bias in estimating the persistence parameter and spurious rejections are the greatest. In addition, this outcome occurs under the null and alternative hypotheses, and more so as the magnitude of the break increases. Consequences of uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(192 citation statements)
references
References 12 publications
2
185
0
5
Order By: Relevance
“…This causes size distortion in such a way that the null hypothesis of unit root is often rejected than necessary. Further, Lee and Strazicich (2001) observed that Lumsdaine and Papell, (1997) calculate the break incorrectly at one period behind the true break which increases the size of break point. Strazicich, (2003, 2004) resolved this problem by proposing a different method of testing for unit root with an endogenous structural break that is not impaired by breaks under the null.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…This causes size distortion in such a way that the null hypothesis of unit root is often rejected than necessary. Further, Lee and Strazicich (2001) observed that Lumsdaine and Papell, (1997) calculate the break incorrectly at one period behind the true break which increases the size of break point. Strazicich, (2003, 2004) resolved this problem by proposing a different method of testing for unit root with an endogenous structural break that is not impaired by breaks under the null.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…26 Thus, in this paper, we use the unit root test with two (endogenously determined) structural breaks proposed by Lee and Strazicich (2003) that have a higher power to detect the unit roots than previous tests. 27 26 See Perron and Ng, 1996;Lee and Strazicich, 2001. 27 For further details, see Lee and Strazicich (2003).…”
Section: Specification Issues and The Var Model Approachmentioning
confidence: 99%
“…The ZA results indicate that the breakpoint occurs in 1988 for Number of station series, in 1974 for overall total series, in 1974 for line length series, in 1932 for passenger wagon series and in 1974 for freight series. To find out whether the inferences are affected by a different lag length procedure, the Schwarz bayesian criterion, as suggested by Lee and Strazicich (2001) was also used to determine the lag length. The break point was determined by the minimum SBC value.…”
Section: Data and Empirical Resultsmentioning
confidence: 99%